2018
DOI: 10.1038/s41598-018-29851-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cuba’s population structure and demographic history using genome-wide data

Abstract: Cuba is the most populated country in the Caribbean and has a rich and heterogeneous genetic heritage. Here, we take advantage of dense genomic data from 860 Cuban individuals to reconstruct the genetic structure and ancestral origins of this population. We found distinct admixture patterns between and within the Cuban provinces. Eastern provinces have higher African and Native American ancestry contributions (average 26% and 10%, respectively) than the rest of the Cuban provinces (average 17% and 5%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 54 publications
3
56
1
Order By: Relevance
“…9 Categorizing Nigeria in this way also corresponds to the historical geographic occupancy of groups with genetic, ethnic, and linguistic differences: the Yoruba in the Bight of Benin and Esan and Igbo in the Bight of Biafra. 4 We considered current Atlantic African populations to be suitable proxies for past populations in Africa given limited migration and current population structure following a latitudinal gradient 13 , 39 , 40 ( Figures S1–S6 ). We combined regions of Europe participating in the transatlantic slave trade by broad historical descriptors 7 and population structure ( Figures S7–S9; Table S3 ), which are largely described by geographic proximity.…”
Section: Methodsmentioning
confidence: 99%
“…9 Categorizing Nigeria in this way also corresponds to the historical geographic occupancy of groups with genetic, ethnic, and linguistic differences: the Yoruba in the Bight of Benin and Esan and Igbo in the Bight of Biafra. 4 We considered current Atlantic African populations to be suitable proxies for past populations in Africa given limited migration and current population structure following a latitudinal gradient 13 , 39 , 40 ( Figures S1–S6 ). We combined regions of Europe participating in the transatlantic slave trade by broad historical descriptors 7 and population structure ( Figures S7–S9; Table S3 ), which are largely described by geographic proximity.…”
Section: Methodsmentioning
confidence: 99%
“…These markers have been successfully studied in various Caribbean groups and revealed considerable variability in the degree and sources of admixture. In the Hispanic Caribbean islands, such as Puerto Rico (Martínez‐Cruzado et al, , ), the Dominican Republic (Tajima et al, ), or Cuba (Fortes‐Lima et al, ; Marcheco‐Teruel et al, ; Mendizabal et al, ), the indigenous component remained relatively high, with up to 60% of maternal Amerindian lineages for the current population of Puerto Rico. However, Mendizabal et al () showed that if 33% of maternal lineages in Cuba could be associated with an Amerindian origin, no Amerindian paternal lineage could be detected, demonstrating a robust sexual bias in the admixture process.…”
Section: Introductionmentioning
confidence: 99%
“…Sex-biased admixture processes are known to have influenced admixed populations, and in particular populations descending from the TAST (MORENO-ESTRADA et al . 2013; FORTES-LIMA et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, intense migrations from Haitian slave-descendants in the 19 th century have already been shown to possibly have contributed to the admixture patterns of other populations in the Caribbean and continental America (MORENO-ESTRADA et al . 2013; FORTES-LIMA et al . 2018).…”
Section: Discussionmentioning
confidence: 99%